Occidentaliser le spectateur : Shirin Neshat, la différence de la différence - Ross, Christine (CV Photo)

(untitled) (Les Productions Ciel variable, 2001)
Imbued by the question of identity and addressing mainly Western viewers, Shirin Neshat's production constantly negotiates the variety of perspectives (masculine, feminine, feminist, Middle Eastern, Western, Asian) that come together at the base of "Moslem" identity. This negotiation, however, strategically maintains the Eastern-Western dualism. The specificity of Neshat's work resides in the conjunction between the identity displacement of Islamic women, on the one hand, and the fixed identity of the Western viewer, on the other hand. The question underlying this text is thus the following: How does Neshat's work articulate the antinomy of change and reification?